The Breathing for Life Trial: a randomised controlled trial of fractional exhaled nitric oxide (FENO)-based management of asthma during pregnancy and its impact on perinatal outcomes and infant and childhood respiratory health. Issue 1 (December 2016) - Murphy, Vanessa; Jensen, Megan; Mattes, Joerg; Hensley, Michael; Giles, Warwick; Peek, Michael; Bisits, Andrew; Callaway, Leonie; McCaffery, Kirsten; Barrett, Helen; Colditz, Paul; Seeho, Sean; et al.
Abstract Background Asthma exacerbations are common during pregnancy and associated with an increased risk of adverse perinatal outcomes. Adjusting asthma treatment based on airway inflammation rather than symptoms reduces the exacerbation rate by 50 %. The Breathing for Life Trial (BLT) will test whether this approach also improves perinatal outcomes. Methods/design BLT is a multicentre, parallel group, randomised controlled trial of asthma management guided by fractional exhaled nitric oxide (FENO, a marker of eosinophilic airway inflammation) compared to usual care, with prospective infant follow-up. Women with physician-diagnosed asthma, asthma symptoms and/or medication use in the previous 12 months, who are 12–22 weeks gestation, will be eligible for inclusion. Women randomised to the control group will have one clinical assessment of their asthma, including self-management education. Any treatment changes will be made by their general practitioner. Women randomised to the intervention group will have clinical assessments every 3–6 weeks during pregnancy, and asthma treatments will be adjusted every second visit based on an algorithm which uses FENO to adjust inhaled corticosteroid (ICS) dose (increase in dose when FENO >29 parts per billion (ppb), decrease in dose when FENO <19 ppb, and no change when FENO is between 19 and 29 ppb). A long acting beta agonist (LABA) will be added when symptoms remain uncontrolled. Both the control and intervention groups will report on exacerbations at a postpartum phone interview. The primary outcome is adverse perinatal outcome (a composite measure including preterm birth, intrauterine growth restriction, neonatal hospitalisation at birth or perinatal mortality), assessed from hospital records. Secondary outcomes will be each component of the primary outcome, maternal exacerbations requiring medical intervention during pregnancy (both smokers and non-smokers), and hospitalisation and emergency department presentation for wheeze, bronchiolitis or croup in the first 12 months of infancy. Outcome assessment and statistical analysis of the primary outcome will be blinded. To detect a reduction in adverse perinatal outcomes from 35 % to 26 %, 600 pregnant women with asthma per group are required. Discussion This trial will provide evidence for the effectiveness of a FENO-based management strategy in improving perinatal outcomes in pregnant women with asthma. If successful, this would improve the management of pregnant women with asthma worldwide. Trial registration Australian New Zealand Clinical Trials RegistryACTRN12613000202763 .